Fluorescence‐guided cancer surgery—A new paradigm. Issue 8 (25th March 2021) - Thammineedi, Subramanyeshwar Rao; Saksena, Ajesh Raj; Nusrath, Syed; Iyer, R. Rajagopalan; Shukla, Srijan; Patnaik, Sujit Chyau; Reddy, R. Pratap; Boleneni, Naren; Sharma, Rakesh M.; Smith, Lynette; Are, Chandrakanth
Abstract: Fluorescence‐guided surgery is an emerging and promising operative adjunct to assist the surgeon in various aspects of oncosurgery, ranging from assessing perfusion, identification, and characterization of tumors and peritoneal metastases, mapping of lymph nodes/leaks, and assistance for fluorescence‐guided surgery (FGS). This study aims to provide an overview of principles, currently available dyes, platforms, and surgical applications and summarizes the available literature on the utility of FGS with a focus on abdomino‐thoracic malignancies.